Sustainable Cities in The Netherlands: Urban Green Spaces Management in Rotterdam - Syahid, Choerunisa Noor; Lissandhi, Ayu Nova; Novianti, Kurnia; Abdul Fikri Angga Reksa (RMPI-BRIN, 2017)
One of challenges of sustainable urban development is to provide a viable environment for the population following the function of space and community activities within it. Research on green space in the Netherlands is important as a response to the global environmental crisis as well as the realization of sustainable development. This research uses an interdisciplinary approach through the analysis of the phenomena of spatial management in the context of local-global sustainable urban development. An interdisciplinary approach is used because the issue of